Stringency of Synthetic Promoter Sequences in Clostridium Revealed and Circumvented by Tuning Promoter Library Mutation Rates - Mordaka,PM; Heap,JT (ACS Synthetic Biology, 2018)
Collections of characterized promoters of different strengths are key resources for synthetic biology, but are not well established for many important organisms, including industrially relevant Clostridium spp. When generating promoters, reporter constructs are used to measure expression, but classical fluorescent reporter proteins are oxygen-dependent and hence inactive in anaerobic bacteria like Clostridium. We directly compared oxygen-independent reporters of different types in Clostridium acetobutylicum and found that glucuronidase (GusA) from E. coli performed best. Using GusA, a library of synthetic promoters was first generated by a typical approach entailing complete randomization of a constitutive thiolase gene promoter (Pthl) except for the consensus -35 and -10 elements. In each synthetic promoter, the chance of each degenerate position matching Pthl was 25%. Surprisingly, none of the tested synthetic promoters from this library were functional in C. acetobutylicum, even though they functioned as expected in E. coli. Next, instead of complete randomization, we specified lower promoter mutation rates using oligonucleotide primers synthesized using custom mixtures of nucleotides. Using these primers, two promoter libraries were constructed in which the chance of each degenerate position matching Pthl was 79% or 58%, instead of 25% as before. Synthetic promoters from these "stringent" libraries functioned well in C. acetobutylicum, covering a wide range of strengths. The promoters functioned similarly in the distantly related species Clostridium sporogenes, and allowed predictable metabolic engineering of C. acetobutylicum for acetoin production. Besides generating the desired promoters and demonstrating their useful properties, this work indicates an unexpected "stringency" of promoter sequences in Clostridium, not reported previously.